Comprehensive evaluation of a compound parabolic concentrator PV window for building energy conservation: optical, thermal, electrical and building energy performance - Li, Xue (2023)
Increasing concerns over energy consumptions and greenhouse gas emissions in buildings have contributed to the emerging of innovative PV glazing technologies to improve the building energy performance. In this thesis, one of the advanced PV glazing systems where an array of concentrating photovoltaic units is sandwiched between two glass panes to form a Crossed Compound Parabolic Concentrating Photovoltaic (CCPC-PV) window was proposed to provide the advanced thermal insulation property, shading capacity as well as producing additional power when compared with a similar structured double-glazed window. A holistic investigation of the CCPC-PV window was conducted in terms of its thermal, optical, and electrical properties as well as the detailed energy and daylight performance of applying CCPC-PV window in buildings. Firstly, an experimental investigation was undertaken in a large climate chamber, and the measurement results were used to validate a three-dimensional Computational Fluid Dynamics (CFD) model. Then the validated 3D CFD model was used to predict the heat transfer mechanism into the CCPC-PV window as well as calculating its total thermal transmittance (or U-value). The optical properties (e.g., optical transmittance and absorptance) of the CCPC-PV window were obtained via a validated ray-tracing model based on the geometry structures and material properties. To calculate the Solar Heat Gain Coefficient (SHGC), ray-tracing results of solar flux absorbed by each layer were transferred into validated CFD simulations as boundary conditions. In addition, a PV modelling algorithm was developed to predict the system output. Finally, the thermal, optical and electrical models were all coupled and transferred into the building simulation software, EnergyPlus, to evaluate the building performance when CCPC-PV windows were applied for under three different climate conditions (hot, temperate and cold). Furthermore, the effects of Window to Wall Ratios (WWRs) as well as the pitch between adjacent CCPC optics were also investigated. Some findings, which have not been reported in previous literature, were drawn from the above detailed investigations of the CCPC-PV window. In terms of the thermal property, both experimental results and CFD simulation results showed that the CCPC-PV windows have a U-value of 2.6 W/m2·K, which is approximately 8% lower than that of a similar structured double-glazed window (2.8 W/m2·K). As for the optical property, ray-tracing simulation results showed that the CCPC-PV windows can provide an optical transmittance between 13% to 55% under normal incident angle condition, which are all lower than that of a double-glazed window (78%). The CFD combined ray-tracing results showed that the SHGC values of the CCPC-PV windows are between 0.46 and 0.68, which are all lower than that of a similar structured double-glazed window (0.81). The above results all indicate that the CCPC-PV windows can reduce the possibility of oversupplied daylight and solar heat in summer when it is installed on the southern façade of an office room. In addition to the advanced thermal and optical properties provided by the CCPC-PV windows, it can produce additional power. The overall investigation of the building performance showed that the appropriate use of the CCPC-PV window on the southern façade can contribute to energy savings of 56.86%, 67.63% and 33.93% under the climate conditions of London, UK, Barcelona, Spain, and Stockholm, Sweden, respectively. Additionally, the use of the CCPC-PV window also led to slightly improved daylight performance when compared to the use of a similarly structured double-glazed window under these three climatic cities. The investigation results from the work in this thesis provide a better understanding of the benefits of the CCPC-PV window applied to buildings when compared to a typical double-glazed window in terms of the energy saving and indoor comfort. In addition, some tentative suggestions were put forward to guide architects and engineers to apply CCPC-PV windows in building façade.